From Paris to Switzerland: Four Pathways to a Forest Reference Level - Stadelmann, Golo; Portier, Jeanne; Didion, Markus; Rogiers, Nele; Thürig, Esther (Frontiers in Forests and Global Change, 2021)
Among terrestrial ecosystems, forests represent large carbon stocks threatened by changing climatic conditions, deforestation, overexploitation and forest degradation. Close to nature forestry may help forests to continue to acting as carbon sinks by promoting their resilience against disturbances. The EU decided to carry out carbon accounting of emissions and removals from managed forests under the Paris Agreement by using a projected Forest Reference Level based on the continuation of current management practices. Methods: We developed four conceptual scenarios that could build a Forest reference level in Switzerland and performed simulations over 50 years using Swiss National Forest Inventory (NFI) data and the empirical forest model MASSIMO. To improve MASSIMO, we further developed a new tree species-specific model for small scale mortality that accounts for the Swiss NFI design. Then, using projected biomass and mortality from MASSIMO, carbon budgets of soil, litter and deadwood were estimated using the Yasso07 model. Results: The U-shaped mortality model performed well (AUC 0.7). Small as well as large trees had the highest mortality probabilities, reflecting both young trees dying due to self-thinning and old trees from age, pests or abiotic influences. All scenarios matched their given harvesting and growing stock targets, whereby the share of broadleaves increased in all regions of Switzerland. This resulted in decreasing biomass growth, possibly due to a species shift from typically fast growing and more shade tolerant conifers to broadleaves. The CO2-balance of the conceptual scenarios ranged from 1.06 to -3.3 Mt CO2 a-1 under Increased Harvesting and Current Management Practices, respectively. Rotation periods are shortened under Increased Harvesting, which is an important climate adaptive management strategy, but forests were predicted to become a net carbon source. In contrast, Current Management Practices resulted in similar harvesting amounts and forests as carbon sinks, as reported in the past. Further, the CMP scenario does not involve political assumptions and fits the EU approach, which makes it comparable to other countries. Therefore, we propose the scenario Current Management Practices as a suitable and ideal candidate for the Swiss FRL.